2020
DOI: 10.1108/jamr-05-2020-0092
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of productivity on profitability in Indian construction firms

Abstract: PurposeThe paper aims to investigate the effect of firm age and size on profitability and productivity of construction firms in India. It also attempts to understand the indirect effect of firm age and size on profitability mediated through firm's productivity.Design/methodology/approachData of 64 construction firms, for a period of 12 years (2006–2017), were collected. In order to measure the direct and indirect effect of size and age on profitability and productivity, a structural equation model was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 76 publications
4
15
0
1
Order By: Relevance
“…The results of the study confirmed that there is a relationship between size and market share growth and profitability, which supports the results of previous studies (Cyril and Singla, 2021; Kotey et al ., 2021; Akhtar et al. , 2022), as well as between age and market share growth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study confirmed that there is a relationship between size and market share growth and profitability, which supports the results of previous studies (Cyril and Singla, 2021; Kotey et al ., 2021; Akhtar et al. , 2022), as well as between age and market share growth.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the study confirmed that there is a relationship between size and market share growth and profitability, which supports the results of previous studies (Cyril and Singla, 2021;Kotey et al, 2021;Akhtar et al, 2022), as well as between age and market share growth. However, it should be noted that the relationship between age and market share growth is negative, meaning that as the age increases, the chances of an increase in market share decreases.…”
Section: Discussionsupporting
confidence: 90%
“…Construction productivity is the efficiency with which a firm converts inputs (resources like workforce, material, machinery, and money) to saleable outputs (work done or revenue earned). When productivity, which represents the execution efficiency of a construction contracting organization, is high, then the balance sheet tends to be healthy [ 47 ]. Three out of the four companies highlighted as lean-focussed are the top three companies in market capitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, companies can take more precise and careful steps to increase sales and profit. Besides that, Cyril and Singla (2021) maintain that firms that are older are more profitable. On the contrary, Rahman & Yilun (2021) found that older firms are less profitable than younger firms.…”
Section: Leverage and Profitabilitymentioning
confidence: 99%
“…The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2020, with a total of 79 companies. The purposive sampling method was used to draw a sample of companies that have been established for at least 26 years in 2020, as we answered call from Cyril and Singla (2021) for study on age and profitability. It also includes only firms that have data available for all years studied (2014 -2020) since sales growth is one of control variable that requires complete data across different years.…”
Section: Population and Samplementioning
confidence: 99%